PERLINDUNGAN KONSUMEN MENGENAI PERTANGGUNGJAWABAN TAGIHAN PEMBAYARAN PENJUMPERAN LISTRIK - Bondan Cahyadi; Ariawan Gunadi (Fakultas Hukum Universitas Tarumanagara, 2022)
Consumer protection according to the Consumer Protection Act itself is all ef orts to ensure legalcertainty for consumers, consumer protection is certainly made to eliminate the gap between businessactors and consumers, where business actors are certainly more dominant than consumers. Therefore,this research was conducted to eliminate the gap between business actors and consumers. There are somany business actors who do not follow the Consumer Protection Act to get more benefits for them.For example, there are consumers who have to pay fines that they have never done before but are stillforced to pay the fines. How is the legal protection? Therefore, this research is intended so that in thefuture there will be no more incidents like this where consumers are very disadvantaged because ofactions taken by business actors. Thus, the Consumer Protection Law must be implemented very wellso that Business Actors do not act arbitrarily to Consumers.